Dietary analysis of young professional soccer players for 1 week during the competitive season - Russel, M.; Pennock, A. (The Journal of Strength and Conditioning Research, 2011)
Limited data exist concerning the dietary practices of young professional soccer players that compete within the United Kingdom. Therefore, the purpose of this study was to investigate the nutritional and activity habits of professional male soccer players (n = 10; age: 17 ± 1 years, height: 1.72 ± 0.01 m, mass: 67.5 ± 1.8 kg, estimated maximal aerobic capacity: 57.8 ± 0.9 ml/kg/min) who played for the youth team of a UK-based Championship club. All players recorded their 7-day dietary intake and activity habits during a competitive week that included a match day, 4- training days, and 2 rest days in the first half of the 2009/2010 playing season. The intake of carbohydrates (5.9 ± 0.4 g/kg/d), proteins (1.7 ± 0.1 g/kg/d), and fats (1.5 ± 0.1 g/kg/d) represented 56 ± 1, 16 ± 1, and 31 ± 1% of the mean daily energy intake respectively. The intake of fiber was found to be significantly lower than Recommended Nutrient Intake (RNI) values (67% of RNI, p < 0.001), whereas all other analyzed micronutrients met or exceeded recommended values. A mean daily energy deficit of 788 ± 174 kcal existed because daily energy expenditures exceeded that of intake (3,618 ± 61 vs. 2831 ± 164 kcal, p = 0.001). The mean daily fluid intake was 3.2 ± 0.3 L. Consequently, the nutritional practices of the sampled group of professional youth soccer players were inadequate to sustain optimized performance throughout training and match play. Youth soccer players should therefore seek to ensure that their diets contain adequate energy through increased total caloric intake, while also optimizing the proportion of energy derived from carbohydrates and ensuring that enough fiber-rich foods are consumed.